Evolution and economic complexity / edited by J. Stanley Metcalfe and John Foster - Foster, John, 1947-; Metcalfe, J. S. (J. Stanley) (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2004)
The book discusses the ontology, analysis, theory of economics.
lje 29/04/13
Loan
Keywords: Evolutionary economics; Complexity (Philosophy)